New food ingredients from broccoli by‐products: physical, chemical and technological properties. (7th February 2019) - Shi, Meng; Hlaing, Mya Myintzu; Ying, DanYang; Ye, JianHui; Sanguansri, Luz; Augustin, Mary Ann
Summary: Broccoli stems and leaves examined were rich in protein (23.2%, dry weight), fibre (36.5%, dry weight) and polyphenols (11.4 mg gallic acid equivalents g −1 ). Chlorogenic acid, neochlorogenic acid and quinic acid were the major phenolics found. Broccoli by‐products have potential to be developed as differentiated food ingredients by separation. On a dry basis, the pomace and washed pomace fractions were enriched in fibre and had higher water‐holding but lower water solubility and emulsifying capacity compared to juice and supernatant from washed pomace, which were enriched in protein. The juice and supernatant had higher polyphenol content and higher antioxidant activity, suggesting that polyphenols were the major contributors to antioxidant activity. For convenience of use, the products may be supplied as packaged powdered ingredients, but this was practical only for broccoli stems and leaves and pomaces as these powders had higher glass transition temperatures than the juice and supernatant fractions. Abstract : Under juicing and water‐washing processes, broccoli edible waste were transferred into fibre‐enriched and polyphenol‐enriched functional food ingredients.